Interactive Marketing - Peter Schafer (Communicare)
Increasing competition, declines in consumer demand and consumers that are more strategic than ever before have led to saturation and stagnation in a number of well-developed markets. Corporations have begun to realise that constructive forms of marketing communication in such markets imply that all business efforts need to be directed at relationship-building with consumers, Le. all communication instruments, including advertising, personal selling, sales promotion and corporate identity as well as conventional direct and database communication need to draw on personalised and targeted methods and media if marketing is to remain cost-effective. Technological developments in interactive communication, telecommunication and digital marketing make this possible. Far more than mere communication tools, interactive media have become powerful business instruments. The article examines the nature of interactive communications and media and their integration and implementation in the marketing communications mix. The long-term implementation of interactive communications in corporations requires a marketing communications specialist that operates more interdisciplinary than ever before: he needs to assume the role of a "marketing communications engineer" beyond the mere technical sense of the term, something that raises a number of implications for the communication services industry academies in communication and marketing communication practitioners.